2018
DOI: 10.1039/c8ra09068h
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of polysaccharides fromCordyceps militarisand their hypolipidemic effects in high fat diet fed mice

Abstract: Structural characterization and comparative evaluation of hypolipidemic activities of intracellular and extracellular polysaccharides from Cordyceps militaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…The liver is an essential organ in the regulation of lipid metabolism, including the metabolism of TG and TC (Huang et al., 2018 ; Ting et al., 2018 ; X. Z. Wan et al., 2020 a; Zeng et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The liver is an essential organ in the regulation of lipid metabolism, including the metabolism of TG and TC (Huang et al., 2018 ; Ting et al., 2018 ; X. Z. Wan et al., 2020 a; Zeng et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many natural polysaccharides and polysaccharide-protein complexes isolated from fungi can be used as a source of therapeutic agents that are relatively non-toxic and show no significant side effects. In recent studies, polysaccharides of C. militaris have been identified to possess antitumor [10], immunomodulatory [11], anti-oxidant [12] and anti-hypolipidemic [13] effects. In this study, the SCR was fermented by C. militaris mycelium using solid fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro experiment and an in vivo study in rodents also confirmed the hypolipidemic activity of the polysaccharide fractions isolated from C. militaris [146,147]. Similarly, Huang et al [148] demonstrated the hypolipidemic activity of intracellular (IPCM) and extracellular polysaccharides (EPCM) from C. militaris in mice fed a high-fat diet.…”
Section: Effect Of C Militaris On the Cardiovascular Systemmentioning
confidence: 66%